Efficacy and safety of expectant management in the treatment of tubal ectopic pregnancy: a systematic review and meta-analysis. Issue 4 (25th October 2020) - Colombo, G E; Leonardi, M; Armour, M; Di Somma, H; Dinh, T; da Silva Costa, F; Wong, L; Armour, S; Condous, G
Abstract: STUDY QUESTION: Is expectant management (EM) of tubal ectopic pregnancy (EP) an effective and safe treatment strategy when compared to alternative interventions? SUMMARY ANSWER: There is insufficient evidence to conclude EM yields a difference in the resolution of tubal EP, the avoidance of surgery or time to resolution of tubal EP when compared to intramuscular methotrexate in stable patients with β-hCG <1500 IU/l. WHAT IS ALREADY KNOWN: The utilisation of medical and surgical management for EP is well established. EM aims to allow spontaneous resolution of the EP without intervention. STUDY DESIGN, SIZE, AND DURATION: We performed a systematic review and meta-analysis, searching Ovid MEDLINE, Embase, PsycINFO, CINAHL, Web of Science, OpenGrey.eu, Google Scholar, cross-referencing citations and trial registries to 15 December 2019. There were no limitations placed on language or publication date. Search terms included tubal EP and EM as well as variations of these terms. PARTICIPANTS/MATERIALS, SETTING AND METHOD: We considered studies that included patients with tubal EP, EM as a comparator, and that were randomised controlled trials (RCTs). The primary outcome was resolution of tubal EP. Secondary outcomes included avoidance of surgery and the time to resolution of EP. Two reviewers independently selected the studies, assessed bias and extracted data. Relative risk (RR) and mean difference with 95% CI were assessed using a random effects model. The certainty of evidence was scored according to Grading of Recommendations Assessment, Development and Evaluation guidelines. MAIN RESULTS AND THE ROLE OF CHANCE: In total, 920 studies were screened. Five studies were eligible for inclusion in the systematic review. Two RCTs comparing methotrexate to EM were identified as being eligible for inclusion in meta-analysis. No RCTs comparing surgery to EM were identified. Compared with EM, there was insufficient evidence that methotrexate yields a difference on resolution of tubal EP (RR 1.04, 95% CI 0.88–1.23, P  = 0.67; two RCTs, moderate-certainty evidence), avoiding surgery (RR 1.10, 95% CI 0.94–1.29, P  = 0.25; two RCTs, low-certainty evidence) or the time to resolution of tubal EP (−2.56 days (favouring EM), 95% CI −7.93–2.80, P  = 0.35; two RCTs, low-certainty evidence). LIMITATIONS, REASONS FOR CAUTION: Only two RCTs with a total of 103 patients were eligible for inclusion in this meta-analysis. Further RCTs comparing EM to medical and surgical management are needed and these should also report adverse events. Patient preference should also be evaluated. WIDER IMPLICATIONS OF THE FINDINGS: We found insufficient evidence of differences in terms of resolution, avoidance of surgery and time to resolution between expectant and medical management. Given the imprecision in the effect estimates as demonstrated by the wide CIs, resulting in the downgrading of certainty of evidence for all outcomes in this meta-analysis, larger RCTs comparing interventions for tubal EP are needed. Caution should be exercised when trying to decide between EM and methotrexate to treat tubal EP. STUDY FUNDING/COMPETING INTEREST(S): There was no funding for this study. NICM receives funding from various sources; none specifically supported this research. M.L. reports grants from Australian Women and Children's Research Foundation, outside the submitted work. M.A.: As a medical research institute, NICM Health Research Institute receives research grants and donations from foundations, universities, government agencies and industry. Sponsors and donors provide untied and tied funding for work to advance the vision and mission of the Institute. This systematic review was not specifically supported by donor or sponsor funding to NICM. M.A. reports a partnership grant with Metagenetics outside the submitted work. G.C. reports grants from Australian Women and Children's Research Foundation, personal fees from Roche and GE Healthcare, outside the submitted work. The remaining authors report no conflicts of interest. PROSPERO REGISTRATION NUMBER: CRD42020142736